Factors affecting sales growth at Escatec Mechatronics Sdn Bhd / Nor Sabarina Zainal Abidin - Zainal Abidin, Nor Sabarina (Faculty of Business and Management, 2006)
In the era of globalizations, competition is fierce. Where every business tends to seek growth, regardless of the size of firms and where the market of operations, every company wants to seek the growth momentum. Fast growth gets the attention of customers, both current and potential; it also boosts customer confidence and enhances a company reputation for excellence. To comprehend the role of growth in a company's evaluation, it is important to understand the factors that affect growth. There are many researches which have been conducted in order to discover the factors that affect sales growth, but the factors that affect company growth are different from each company. The factors that affect growth can be view in two directions which is from external factors which factors that beyond the management control and internal factors which is the management factors that affect a firm's ability to obtain sales growth. Thus, in this research, both external factors and internal factors will be discover based from the availability of the secondary data which taken from internal source and external published source, and for analysis purpose the researcher has use multiple regression since there are more than one independent in this research. At the end of the research, the researcher has found that there are two internal factors that have a significant relationship with the Sales, which is Inventory and Delivery. The research has found that the two variables can influence sales, this shows that the Inventory and Delivery is very important to the firm to monitor and control. Thus, the firm should focus on these two variables in order to increase more sales. Based from the findings several recommendations have been made for the firms and also for future research purpose.